2019
DOI: 10.1186/s12884-019-2355-y
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal depressive symptoms among low-income South African women at risk of depression: trajectories and predictors

Abstract: Background The aim of the study was to identify trajectories of perinatal depressive symptoms and their predictors among women living in a low-resource setting in South Africa, and who present with a risk of depression during pregnancy. Methods This is a secondary analysis of a randomised controlled trial among 384 women living in Khayelitsha, a low income setting in South Africa, recruited at their first antenatal visit if they scored 13 or above on the Edinburgh Postn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 70 publications
3
49
3
Order By: Relevance
“…In 11 studies (29.7%), FI was analysed as a dichotomous variable defined as either FS or FI. Finally, in three publications, FI was treated a dichotomous variable in different ways: one study (2.7%) categorized FI as mild FI versus moderate or severe FI [42]; two studies (5.4%), the adopted dichotomization was food securityFS or mild FI versus moderate or severe FI [37,43]; and in one study (2.7%), FI was considered either severe or not severe [44].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 11 studies (29.7%), FI was analysed as a dichotomous variable defined as either FS or FI. Finally, in three publications, FI was treated a dichotomous variable in different ways: one study (2.7%) categorized FI as mild FI versus moderate or severe FI [42]; two studies (5.4%), the adopted dichotomization was food securityFS or mild FI versus moderate or severe FI [37,43]; and in one study (2.7%), FI was considered either severe or not severe [44].…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of these results allows us to verify the importance of minimizing stress factors in pregnant women's. FI, in turn, was shown to increase chances of depression [30,36,42,44,53,58,60], stress [45,61] and anxiety [33]. In addition to the mental health complications of pregnant women, symptoms of stress and depression increased the release of hormones such as corticotropin [13] and could lead to clinical complications such as hyperglycaemia and hypertension [45,55].…”
Section: Discussionmentioning
confidence: 99%
“…Depression Research and Treatment surveys [22,[26][27][28][29][30][31]. Research in both urban and rural areas of South Africa has shown that the EPDS is a validated screening instrument [32][33][34][35][36], whereas other sub-Saharan countries have also validated the EPDS to screen for depression during and after pregnancy [19,[32][33][34][35]. The EPDS comprises ten self-report items that evaluate depressive symptoms in the past seven days.…”
Section: Measurement Instrument the Edinburgh Postnatalmentioning
confidence: 99%
“…Studies which have used more complex longitudinal analyses, such as growth curve mixture modelling (GCMM), have enabled the identification of latent subgroups of women with both chronic and transient symptom trajectories during the perinatal period, in both HICs [30] and LMICs [31,32]. This allowed investigators to disentangle severity from chronicity and moving away from the dichotomisation of depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%